THE ANALYSIS OF PSYCHOLOGICAL DISORDER IN THE MOVIE: A STAR IS BORN - Erna Pranata Putri (Asosiasi Dosen Muda Indonesia, 2022)
People act differently from one another for their own reason. Determining what and why other people do or feel is not easy. Moreover, understanding our own feeling and behaviour is also not always easy. Some people show normal behaviour and some people show psychological disorder. By studying about their behaviour, people can have a chance to live in normal. For this reason, this research was conducted to analyze Jackson Maine’s psychological disorder in the movie A star is Born. Jackson is portrayed as a singer who is battling an alcohol and drug addiction. This behaviour was analyzed using a theory proposed by Davison, Neale, and Kring about the characteristics of psychological disorder.